2002
DOI: 10.1152/ajprenal.00152.2001
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin transporter PGT is expressed in cell types that synthesize and release prostanoids

Abstract: is a broadly expressed transporter of prostaglandins (PGs) and thromboxane that is energetically poised to take up prostanoids across the plasma membrane. To gain insight into the function of PGT, we generated mouse monoclonal antibody 20 against a portion of putative extracellular loop 5 of rat PGT. Immunoblots of endogenous PGT in rat kidney revealed a 65-kDa protein in a zonal pattern corresponding to PG synthesis rates (papilla Х medulla Ͼ cortex). Immunocytochemically, PGT in rat kidneys was expressed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
50
0
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 34 publications
5
50
0
2
Order By: Relevance
“…COX-1 was expressed in a perinuclear pattern consistent with its known localization to the nuclear envelope (21). PGT was expressed at the apical membrane as reported previously by our laboratory (10). PGDH was expressed throughout the cytoplasm of cortical collecting duct cells.…”
Section: Resultssupporting
confidence: 82%
See 3 more Smart Citations
“…COX-1 was expressed in a perinuclear pattern consistent with its known localization to the nuclear envelope (21). PGT was expressed at the apical membrane as reported previously by our laboratory (10). PGDH was expressed throughout the cytoplasm of cortical collecting duct cells.…”
Section: Resultssupporting
confidence: 82%
“…B, immunolocalization of endogenous PGT in rat kidney cortical collecting ducts using a mouse monoclonal antibody. Arrows indicate localization at or near the apical plasma membrane (10). C, immunolocalization of endogenous PGDH in rat kidney cortex.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, we used in our experiments microsomal preparations from four different brain regions (cortex, hippocampus, cerebellum and brainstem/diencephalon) and demonstrated that the cortex has the highest expression of PGT in the mouse brain. We would like to note that PGT expression may be highly coordinated with the synthesis and release of prostaglandins since Bao et al (2002) have shown that PGT expression is limited to cells that synthesize and release prostaglandins. The same investigators have also shown that cyclooxygenase-2 (COX-2) -an inducible enzyme which catalyses PG formation in the brain, as well as PGT, are coordinately induced in Swiss 3T3 cells in-vitro (Schuster, 1998).…”
Section: Discussionmentioning
confidence: 99%